Plagiarism issues in post-1998 Indonesian film posters - Imanjaya, Ekky; Pratalaharja, Emanuel (Wacana, Journal of the Humanities of Indonesia, 2012)
There are online articles, with visual materials, stating that some post-1998 Indonesian film posters were accused as plagiarism by common people. However, academically speaking, it needs deeper skills and knowledge to prove acts of plagiarism. This paper will discuss the issues around Indonesian film posters and plagiarism, including the possibility of citing in graphic design. The research will treat film posters not only as marketing tools to promote the movies, as many people consider, but also as graphic design materials. Some terms such as appropriation, homage, and pastiche will be discussed to analyze the phenomenon.